Elevated Fasting Plasma Glucose Is Associated With an Increased Risk of MCI: A Community-Based Cross-Sectional Study - Li, Wei; Yue, Ling; Sun, Lin; Xiao, Shifu (Frontiers in Endocrinology, 2021)
Abstract Background: Mild cognitive impairment (MCI) is a transitional state between normal elderly people and dementia, with a higher risk of dementia transition. The primary purpose of the current study was to investigate whether routine blood and blood biochemical markers could be used to predict the onset of MCI. Methods: Data were obtained from the cohort study on the brain health of the elderly in Shanghai. A total of 1015 community elders were included in the current study. Based on clinical evaluation and the scores of Montreal Cognitive Assessment (MoCA), these participants were divided into the MCI (n=444) and cognitively normal groups (n=571). Then we tested their fasting blood routine and blood biochemical indexes, and collected their general demographic data by using a standard questionnaire. Results: By using binary logistic regression analysis and the ROC curve, we found that elevated fasting plasma glucose(p=0.025, OR=1.118, OR=1.014-1.233) was a risk factor for MCI. Conclusions: Elevated fasting blood glucose may be a risk factor for mild cognitive impairment, but the above conclusions need to be verified by longitudinal studies. Keywords: fasting plasma glucose, MCI, cross-sectional, elderly, Chinese